In vitro study on radiographic gray levels of biomaterials using two digital image methods - Nobrega, Newton Fernando Sobreira [UNIFESP] (2012)
PURPOSE: To compare the direct and indirect radiographic methods for assessing the gray levels of biomaterials employing the Digora for Windows and the Adobe Photoshop CS2 systems. METHODS: Specimens of biomaterials were made following manusfacturer's instructions and placed on phosphor storage plates (PSP) and on radiographic film for subsequent gray level assessment using the direct and indirect radiographic method, respectively. The radiographic density of each biomaterial was analyzed using Adobe Photoshop CS2 and Digora for Windows software. RESULTS: The distribution of gray levels found using the direct and indirect methods suggests that higher exposure times are correlated to lower reproducibility rates between groups. CONCLUSION: The indirect method is a feasible alternative to the direct method in assessing the radiographic gray levels of biomaterials, insofar as significant reproducibility was observed between groups for the exposure times of 0.2 to 0.5 seconds.